THE INHIBITION AND ADSORPTION PROPERTIES OF DTPMP TSC ON STAINLESS STEEL IN ACIDIC MEDIUM - kumar, P. Selva (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The inhibition effect of diethylenetriamine penta(methylene phosphonic acid) (DTPMP) and Trisodium Citrate (TSC) on the corrosion behavior of stainless steel in 0.5 M H2SO4 solution was investigated by using weight loss method. The combined corrosion inhibition efficiency offered 200 ppm of DTPMP and 150 ppm of TSC was 95%. Polarization study showed that the inhibitors inhibit stainless steel corrosion through mixed mode and electrochemical impedance spectroscopy (EIS) results confirm the adsorption of the inhibitors at stainless steel/acid interface. The adsorption of DTPMP and TSC onto the stainless steel surface was found to follow Langmuir adsorption isotherm modes. Negative values of (Î”Gads) in the acid media ensured the spontaneity of the adsorption process. The nature of the protective film formed on the metal surface has been analyzed by FTIR spectra, SEM and AFM analysis. The activation energy (Ea), free energy change (Î”Gads), enthalpy change (Î”Hads) and entropy change (Î”Sads) were calculated to understand the corrosion inhibition mechanism.